Derajat Demokratisasi Desa di Indonesia - Noman Kresna Martha (Universitas Islam Darul Ulum Lamongan, 2020)
National democracy will be strong if it is supported by democracy at the grassroots level. Nearly the last two decades, counting since the 1998 reforms, public attention has focused on democratic systems and journeys at the national level. While in the lowest society, democracy has not been a prominent agenda either in regulation or in the real political process. Village Communities, for example, have so far only been 'involved' in regional and national 'democratic' events, such as in elections, direct Pemilukada, or become objects of regulation in regional autonomy. At the level of jargon, democracy is often interpreted as a government of and for the people, meaning government by the people and carried out by representatives who are freely elected by the people. Democratization, because it is an effort to achieve democratic life through democratic means. Democracy is not achieved through a non-democratic process and the application of democratic methods does not always struggle in a democratic situation.